Research of Adverse Social Effects and Prevention Challenges in the Context of Sustainable Societal Development - Kipāne, Aldona; Vilks, Andrejs (European Journal of Sustainable Development, 2023)
The sustainable development of society is determined by activities aimed at ensuring the well-being of society, integrated and balanced evolution of the environment and economy, at the same time, without jeopardising the possibilities of meeting the needs of future generations. Improving the quality of life of every member of society by improving economic activities, promoting social cohesion and security are of great importance. In today’s society, crime, corruption and other adverse social phenomena have a major impact on the sustainable development of society by reducing investment in the development and implementation of full-fledged growth programmes. During the crisis and post-crisis period, social pathologies are growing and their adverse effects are increasing too. The true indicators of their prevalence and negative impact are objectively sufficiently not known. Adverse social phenomena have a particularly negative impact on the sustainable development of society, which has various and diverse forms of influence. Large financial, material, intellectual and other resources, which could be used in the sustainable development of society, are accumulated in the research of adverse phenomena, assessment of their impact, combating and prevention. Keywords: development, prevention, research, social effects, social sustainability.